2008
DOI: 10.1110/ps.036749.108
|View full text |Cite
|
Sign up to set email alerts
|

Helix XI contributes to the entrance of the serotonin transporter permeation pathway

Abstract: The sodium-dependent transporters for dopamine, norepinephrine, and serotonin that regulate neurotransmission, also translocate the neurotoxin 1-methyl-4-phenylpyridinium (MPP + ). Previous studies implicated residues in transmembrane helix (TMH) XI of DAT as important sites for MPP + transport. We examined the importance of TMH XI residues F551 and F556 for MPP + translocation by human SERT. Mutations at hSERT F556, but not F551, reduced both 5-HT and MPP + transport compared to wild type. However, F556S/hSER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…To examine the distance between residues identified at the entrance to the pore, we took advantage of the available Cys single mutants and generated Cys double mutants in the C109A background (Table 1). Our laboratory has previously observed that hSERT F556C is sensitive to inactivation by MTSET (9). In the present study, F556C as well as (Fig.…”
Section: Sensitivity Of Hsert Cys Mutants To Mts Reagents-tosupporting
confidence: 74%
See 2 more Smart Citations
“…To examine the distance between residues identified at the entrance to the pore, we took advantage of the available Cys single mutants and generated Cys double mutants in the C109A background (Table 1). Our laboratory has previously observed that hSERT F556C is sensitive to inactivation by MTSET (9). In the present study, F556C as well as (Fig.…”
Section: Sensitivity Of Hsert Cys Mutants To Mts Reagents-tosupporting
confidence: 74%
“…In this study, a homology model of SERT based on the crystal structure of a member of the neurotransmitter sodium symporter family was used to obtain insights into the extracellular entrance to the substrate permeation pathway (9,10). Our model suggests that the entrance to the pore is lined by TMHs I, III, VI, X, and XI as well as EL4 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A widely used approach has been the substituted-cysteine accessibility method (SCAM), where cysteines are introduced in different positions and selectively derivatized with thiol reactive compounds, to provide information on protein structure. [98][99][100] Several SCAM studies on SERT [101][102][103][104][105][106][107][108][109] and NET 110 have verified the overall 12 TMD topology as well as identified a number of amino acid positions as potential candidates for binding site residues.…”
Section: Initial Structure and Function Relationships In Monoamine Tr...mentioning
confidence: 96%